2020
DOI: 10.1111/tbed.13569
|View full text |Cite
|
Sign up to set email alerts
|

The red fox ( Vulpes vulpes ) as a potential natural reservoir of human cryptosporidiosis by Cryptosporidium hominis in Northwest Spain

Abstract: Giardia duodenalis and Cryptosporidium spp. are ubiquitous intestinal protozoa that parasitize domestic and wild animals, as well as human beings. Due to their zoonotic potential, the objective of the present study was to determine the presence of these pathogens in the fox population (Vulpes vulpes) located in Northwest Spain. A total of 197 faecal samples from legally hunted foxes were collected in the autonomous region of Galicia. The presence of G. duodenalis and Cryptosporidium spp. was investigated by PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
2
12
1
Order By: Relevance
“…In this regard, Vicente et al [16] and Millán and Casanova [17] previously informed that cats might play an important role in the life cycle of some parasites, namely the ones with a direct life cycle (A. tubaeforme and T. cati). This may be an indicator of overlapping between sylvatic and domestic (or peri-domestic) transmission cycles of these parasites, as previously suggested by Barrera et al [34] for the protist species Cryptosporidium hominis found in red foxes in Galicia. Millán and Casanova [17] found an overall higher parasite prevalence in feral cat samples (84%) than in Iberian lynx samples and several parasites that both felines share, which means that domestic/feral and wild cats may be an important reservoir of parasites that can affect the Iberian lynx.…”
Section: Discussionsupporting
confidence: 63%
“…In this regard, Vicente et al [16] and Millán and Casanova [17] previously informed that cats might play an important role in the life cycle of some parasites, namely the ones with a direct life cycle (A. tubaeforme and T. cati). This may be an indicator of overlapping between sylvatic and domestic (or peri-domestic) transmission cycles of these parasites, as previously suggested by Barrera et al [34] for the protist species Cryptosporidium hominis found in red foxes in Galicia. Millán and Casanova [17] found an overall higher parasite prevalence in feral cat samples (84%) than in Iberian lynx samples and several parasites that both felines share, which means that domestic/feral and wild cats may be an important reservoir of parasites that can affect the Iberian lynx.…”
Section: Discussionsupporting
confidence: 63%
“…Cryptosporidium hominis is the dominant species in humans in many industrialised countries and in developing countries, whereas, in the Middle East, European countries and New Zealand, C. parvum occurs at similar rates to C. hominis [ 1 ], indicating that zoonotic transmission is more prevalent in countries with intensive farming [ 122 ]. Although largely anthropologically transmitted, there have been numerous reports of C. hominis in animals (including non-human primates, cattle, sheep, goats, horses, donkeys, Bactrian camels, birds, marsupials, a dugong, badger, dingo, foxes, flying fox, rodents, and fish) and experimental infections has been established in calves, lambs, piglets, gerbils, and mice [ 123 , 124 , 125 ]. In human infectivity trials, the 50% infectious dose (ID 50 ) was as low as 10 C. hominis oocysts [ 126 ], however, in animal models, much larger numbers of oocysts were required to achieve infections, suggesting that higher doses are required to cause infection in animals [ 125 ].…”
Section: Zoonotic Cryptosporidium Species and Genotypesmentioning
confidence: 99%
“…Altogether, 10 Cryptosporidium species ( C. canis , C. parvum , C. hominis , C. meleagridis , C. felis , C. ubiquitum , C. andersoni , C. suis , C. tyzzeri , and C. galli ) and four Cryptosporidium genotypes (mink genotype, muskrat genotype I, fox genotype, and ferret genotype) have been identified in minks, raccoon dogs and foxes worldwide ( Barrera et al., 2020 ; Qian et al., 2020 ; Kvac et al., 2021 ). Among them, C. canis , C. meleagridis , C. parvum and mink genotype have been detected in farmed minks, raccoon dogs and foxes in China, with C. canis and mink genotype being the dominant ones ( Zhang et al., 2016a ; Zhang et al., 2016b ; Yang et al., 2018 ; Qian et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%